“TV should exhibit the image of an active, curious and competent child” - Fuenzalida, Valerio (2019)
Valerio Fuenzalida is one of the most important researchers of media education in Latin America. From his first experiences on television channels, in the 1970s, to his current interest in children’s audiences, there are some constants: not being afraid of new things, distrusting paradigms, and asking and researching in order to have a grounded argument. In this interview, he told us how he developed the ideas that led him to propose an active reception while working at the Center for Research on Cultural and Artistic Expression (Ceneca). In addition, he showed us how he has delved into the importance of emotions in the relationship that people establish with the audiovisual. Valerio remains intellectually restless, with a desire to continue building thought and transmitting it directly or through the possibilities of technology.